MaTriG: Game Edukasi Matematika dengan Construct 3 - Permatasari, Shinta; Asikin, Mohammad; Dewi , Nuriana Rachmani (AI Society & STMIK Indonesia, 2022)
Mathematics is a structured subject and is still interconnected between materials, sometimes there are students' assumptions about math lessons that are very difficult so students are lazy to learn making the learning environment unattractive for students. The teacher must start to make something interesting for students. Along with the development of technology, many things can be made to support learning, one of which is games. This study uses the Research and Development (R&D) method. The MaTtriG educational game was developed using software construct 3. The MaTriG game was designed with the help of Adobe Illustrator 2020. This MaTriG educational game is of the platformers game genre, the educational side of this game includes math material, one of which is a two-variable linear equation system for class VIII. A platform for creating MaTriG educational game applications with Android that can be played and learned anywhere.